Building Inclusivity and Empathy Through Writers' Workshop. (6th February 2021) - Beschorner, Beth; Hall, Anna
Abstract: All children have the right to experience a safe and inclusive classroom that engages them in learning and advances equity. Writers' workshop is particularly well suited for creating a safe and inclusive space. Writers' workshop encourages children to share their own stories and listen to, learn about, and develop empathy for others. This instructional strategy can also encourage conversation about important social issues in local communities and the broader world. This article explains specific approaches that can be used within the writers' workshop framework to examine assumptions, use inclusive language, and practice respectful interactions.